Control of Root Stem Cell Differentiation and Lateral Root Emergence by CLE16/17 Peptides in Arabidopsis - Zhang, Lihua; Yang, Yi; Mu, Changqing; Liu, Mingyu; Ishida, Takashi; Sawa, Shinichiro; Zhu, Yuxian; Pi, Limin (Frontiers in Plant Science, 2022)
Secreted peptide-mediated cell-to-cell communication plays a crucial role in multicellular organisms. A large number of secreted peptides have been predicated by bioinformatic analysis in plants. However, only a few of them have been functionally characterized. In this study, we show that two CLE peptides CLE16/17 are required for both stem cell differentiation and LR emergence in Arabidopsis. We further demonstrate that the CLE16/17 peptides act through the CLV1-ACR4 protein kinase complex in CSC differentiation, but not in LR emergence. Furthermore, we show that CLE16/17 promote LR emergence probably via activating the expression of HAE/HSL2 required for cell wall remodeling. Collectively, our results reveal a CLV1-ACR4-dependent and -independent dual-function of the CLE16/17 peptides in root development.